ASSESSING THE COMMITMENT, MATURATION AND INFECTIVITY OF SEXUAL STAGES OF MALARIA PARASITES IN SCHOOLCHILDREN LIVING IN A HIGH MALARIA TRANSMISSION AREA OF BURKINA FASO. (12th February 2017) - Barry, Aissata; Tiono, Alfred; Sirima, Sodiomon; Bousema, Teun
Abstract : Background: With the move towards malaria elimination, it becomes essential to understand the contribution of asymptomatic parasite carriers to disease transmission. However, the dynamics of infection and gametocyte development are poorly understood in asymptomatic versus symptomatic malaria infections. This was addressed in a longitudinal study of school children in Balonghin, district of Saponé, Burkina Faso. Methods: The study involved healthy schoolchildren (with no malaria parasite at microscopy) age 5–10 years. For the first year survey, children were cleared for subpatent infections using standard malaria therapy. No clearance will occur for the second year survey. Children are followed up for 6 months during which repeated finger prick blood samples for the detection and characterisation of infections are collected. Also at three occasions a venous blood sample is collected for direct membrane feeding assay (DMFA) to assess infectiousness to mosquitoes. Results: The first year survey was completed. Fifty (50) children were recruited and followed up. Almost all the children develop infection and symptomatic malaria during the follow-up period post clearance of initial infection. None of the children has infected mosquitoes during the DMFA assays. The second year survey is in process. The full results will be presented during the forum. Conclusions: These data will be pivotal in understanding human infectious reservoir. This will help designing interventions to tackle the spread of malaria from symptomatic and asymptomatic malaria individuals towards global in eliminating malaria.